MANAGEMENTUL PROIECTULUI - O INOVAŢIE ÎN CURRICULUMUL PSIHOPEDAGOGIC UNIVERSITAR - USM ADMIN (Moldova State University, 2009)
This article responds to the challenge but also to the opportunity to teach the academic discipline for the second cycle of university studies, with theoretical-applicative character. "Project Management" is an attempt that contributed, we hope, to the accomplishment of specific educational objectives, promoted at the European level during the Year of Creativity and Innovation. The author positively affirms that in the period we are going through, with effervescent changes at all levels, including those in societies in transition, the university discipline "Project Management", intended for socio-humanistic departments, offers students big chances for professional qualification. It provokes students to research, create and study both individually and in teams. This subject also favors concrete actions according to some functional reference terms. Project management has become an omnipresent problem in the educational activity at any scholar level and at the university level; it will further be approached in a generalized and integrated manner with ample interdisciplinary references in the educational sciences domain, as well as in different types of management.